PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PELATIHAN, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN LPD DESA PAKRAMAN PADANGSAMBIAN DI DENPASAR - Ni Wayan Henny Sukraeni; Ni Nyoman Suryani; I Nyoman Mustika (EMAS, 2022)
Performance or in English is performance, namely the results of work that can be achieved by a person or group of people in the organization, in accordance with their respective authorities and responsibilities in an effort to achieve the goals of the organization concerned legally, not violating the law and in accordance with morals and ethics. The high and low performance is certainly influenced by various factors, including leadership, training and employee competence. This study aims to determine the effect of transformational leadership, training and competence on employee performance of LPD Desa Pakraman Padang Sambian in Denpasar. The research sample was the employees of the LPD Desa Pakraman Padang Sambian in Denpasar, totaling 35 people who were determined by census. The collected data were analyzed by multiple linear regression. The results of the analysis show that; 1. Transformational Leadership has a positive and significant effect on employee performance of LPD Desa Pakraman Padang Sambian in Denpasar. This shows that the better the transformational leadership is implemented, the employee's performance will increase. 2. Training has a positive and significant effect on employee Performance of LPD Desa Pakraman Padang Sambian in Denpasar. This shows that the better the implementation of the training carried out by the company, the employee's performance will increase. 3. Competence has a positive and significant effect on employee performance of LPD Desa Pakraman Padang Sambian in Denpasar. This shows that the better the attention to the competencies possessed by the employees, the higher the employee's performance.